Body mass index: secular trends in children and adolescents from Brazil - Gabriel Gustavo Bergmann; Mauren Lúcia de Araújo Bergmann; Eraldo dos santos Pinheiro; Rodrigo Baptista Moreira; Alexandre Carriconde Marques; Daniel Carlos Garlipp; Adroaldo César Araújo Gaya (Universidade Federal de Santa Catarina, 2009)
The aim of this study was to compare the 07 to 17 years old Brazilian children and adolescents BMI distribution assessed at 1989 and 2004/2005. The BMI distribution were compared using two large surveys realized at Brazil. One of it was realized at 1989 and the other was realized at 2004/2005. The samples were composed for 16.012 and for 54.574 at first and second surveys, respectively. The BMI distribution was made using the percentiles 15 (p15), 50 (p50), and 85 (p85). At p15 closely there were not changes in the BMI values, at p50 and p85 in the other hand, occurred enhances in the BMI values. Boys increased along all ages. Girls increased only until 11/12 years old. The increases at p85 were bigger than at p50 in both sexes. The results of the present study demonstrated that, as in others countries, at Brazil seems to be having increase in the children and adolescents BMI values with the pass of the years, probably increasing the overweight and obesity prevalence in this age band.